Massachusetts State House, Beacon Street, 1859 - Unknown (Tufts Archival Research Center, 2005)
Large crowd has gathered at the front of the State House for the dedication. Dedication of the Daniel Webster statue in the State House grounds is of bronze, by Hiram Powers. It is the second of Webster executed by the sculptor, the first having been lost at sea while beeing brought from Leghorn. It was placed in position, in 1859, and the cost $10,000. From King's Hanbook, 9th edition. 18 1/4 x 22 3/4 Photographs